In vitro/in vivo evaluation of agar nanospheres for pulmonary delivery of bupropion HCl. (23rd July 2016) - Varshosaz, Jaleh; Minaiyan, Mohsen; Zaki, Mohammad Reza; Fathi, Milad; Jaleh, Hossein
Abstract: Bupropion HCl is an atypical antidepressant drug with rapid and high first-pass metabolism. Sustained release dosage form of this drug is suggested for reducing its side effects which are mainly seizures. The aim of the present study was to design pulmonary agar nanospheres of bupropion HCl with effective systemic absorption and extended release properties. Bupropion HCl was encapsulated in agar nanospheres by ionic gelation, and characterized for physical and release properties. Pharmacokinetic studies on nanospheres were performed on rats by intratracheal spraying of 5 mg/kg of drug in form of nanospheres compared to intravenous and pulmonary delivery of the same dose as simple solution of the drug. The optimized nanoparticles showed particle size of 320 ± 90 nm with polydispersity index of 0.85, the zeta potential of −29.6 mV, drug loading efficiency of 43.1 ± 0.28% and release efficiency of 66.7 ± 2%. The area under the serum concentration–time profile for the pulmonary nanospheres versus simple solution was 10 237.84 versus 28.8 µg/ml min, T max of 360 versus 60 min and the C max of 1927.93 versus9.93 ng/ml, respectively. The absolute bioavailability of the drug was 86.69% for nanospheres and 0.25% for pulmonary simple solution. Our results indicate that pulmonary delivery of bupropion loaded agar nanospheres achieves systemic exposure and extends serum levels of the drug.